Penyakit Virus Ebola - Meis Rafelin Pada (LPPM Universitas Negeri Jakarta, 2020)
ABSTRACTThe genus Ebolavirus from the family Filoviridae is composed of five species including Sudan Ebolavirus, Reston Ebolavirus, Bundibugyo Ebolavirus, Taï Forest Ebolavirus, and Zaire Ebolavirus The transmission of these viruses to human body is via direct contact with blood, secret,organ, or other body fluid of the infected person. The mortality of Ebola infection is still high in human and the emergence of a new condition known as “Post-Ebola virus disease syndrome” Keywords: Ebola virus, ebola virus disease, post Ebola virus disease syndrome